Recent finance advances in information technology for inclusive development: A systematic review - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2018)
The overarching question tackled in this paper is: to what degree has financial development contributed to providing opportunities of human development for those on low-incomes and by what information technology mechanisms? We systematically review about 180 recently published papers to provide recent information technology advances in finance for inclusive development. Retained financial innovations are structured along three themes. They are: (i) the rural-urban divide, (ii) women empowerment and (iii) human capital in terms of skills and training. The financial instruments are articulated with case studies, innovations and investment strategies with particular emphasis, inter alia on: informal finance, microfinance, mobile banking, crowdfunding, micro insurance, Islamic finance, remittances, Payment for Environmental Services (PES) and the Diaspora Investment in Agriculture (D IA) initiative.
Keywords: G20; I10; I20; I30; O10; 330; Finance; Inclusive Growth; Economic Development